2021
DOI: 10.1371/journal.pone.0249237
|View full text |Cite
|
Sign up to set email alerts
|

Remote assessment in adults with Autism or ADHD: A service user satisfaction survey

Abstract: Advances in digital health have enabled clinicians to move away from a reliance on face to face consultation methods towards making use of modern video and web-based conferencing technology. In the context of the COVID-19 pandemic, remote telecommunication methods have become much more common place in mental health settings. The current study sought to investigate whether remote telecommunication methods are preferable to face to face consultations for adults referred to an Autism and ADHD Service during the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Similar to the findings of this study, professionals elsewhere have raised concerns about the validity and reliability of telehealth autism diagnostic assessments and difficulties in assessing core autism traits remotely [ 13 , 15 - 19 ]. Concerns have likely been amplified by the fact that professionals are unable to use mainstay diagnostic tools, notably the ADOS-2 [ 27 ], and they may not yet be trained in alternatives with preliminary validation (eg, the Brief Observation of Symptoms of Autism) [ 22 ].…”
Section: Discussionsupporting
confidence: 73%
“…Similar to the findings of this study, professionals elsewhere have raised concerns about the validity and reliability of telehealth autism diagnostic assessments and difficulties in assessing core autism traits remotely [ 13 , 15 - 19 ]. Concerns have likely been amplified by the fact that professionals are unable to use mainstay diagnostic tools, notably the ADOS-2 [ 27 ], and they may not yet be trained in alternatives with preliminary validation (eg, the Brief Observation of Symptoms of Autism) [ 22 ].…”
Section: Discussionsupporting
confidence: 73%
“…In both cases, telehealth offered them opportunities to continue or expand their practice. Patients receiving services via telemedicine and telehealth have reported high levels of satisfaction with this modality (Rodrigues et al, 2021), and, in at least one recent study, a majority of respondents indicated a preference for receiving health‐related services remotely (Adamou et al, 2021). As noted previously, future research is needed on more efficient training modalities (e.g., asynchronous training) to promote the dissemination of this curriculum and on the long‐term maintenance and generality of this training.…”
Section: Discussionmentioning
confidence: 99%
“…While limited in scope, existing reviews focused on telehealth for persons with ASC have concluded that it is a promising delivery approach for both diagnosis and treatment of the condition (La Valle et al, 2022 ; Sutherland et al, 2018 ). Several newly published studies back these findings, with moderate to high satisfaction reported following diagnostic evaluations (Adamou et al, 2021 ; Jang et al, 2021 ) and treatment (Lynch et al, 2021 ; Pollard et al, 2021 ; Srinivasan et al, 2021 ) for those with ASCs. Unfortunately, relatively few studies or reviews have been conducted to determine the satisfaction of telehealth among individuals who have IDDs.…”
mentioning
confidence: 87%